Semantic Analysis of Hyponymy on Hansel and Gretel Tale by Brothers Grimm - Codiñera, Airis Kim (International Journal of English Language Studies, 2025)
Semantics is the part of linguistics that is concerned with meaning. A hyponym can be an applicable teaching technique to enrich students' vocabulary that is related to the area of a semantic field. Hyponymy has many categories, and it is difficult to determine which category a word is in. Hence, this descriptive study explored the usage of hyponymy in the tale titled "Hansel and Gretel" by Jacob and Wilhelm Grimm. The purpose of this research was to find out the dominant and least hyponymic categories and figure out why the dominant category of hyponymy is used in the three short stories. To provide better analysis, the researcher used semantic analysis to analyze the data. The researcher found 80 words as the data, which fell into 19 categories of hyponymy, such as number, family, sex/gender, types of location, parts of a house, time of the day, colors, celestial bodies, parts of the human body, vehicles, prepositions of place, kinds of taste, animals, fruits, sizes, clothing/human wear, mythical creatures, pastries and period. Parts of the human body were the dominant category of hyponymy that existed in the tale, and these are the least categories that existed in the story: colors, celestial bodies, vehicles, kinds of taste, mythical creatures, pastries, and periods. Moreover, a single word included in a hyponymy category is used to complete a sentence, and its meaning can be understood to develop story ideas by the author of the tale "Hansel and Gretel." The study concluded that hyponyms contribute significantly to the richness of vocabulary and semantic depth in literary texts. This paper recommends that language and literature teachers incorporate hyponymy as a strategy in vocabulary enrichment activities.